2005
DOI: 10.1213/01.ane.0000186348.86792.38
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Administration of Local Anesthetics to Relieve Neuropathic Pain: A Systematic Review and Meta-Analysis

Abstract: We reviewed randomized controlled trials to determine the efficacy and safety of systemically administered local anesthetics compared with placebo or active drugs. Of 41 retrieved studies, 27 trials of diverse quality were included in the systematic review. Ten lidocaine and nine mexiletine trials had data suitable for meta-analysis (n = 706 patients total). Lidocaine (most commonly 5 mg/kg IV over 30-60 min) and mexiletine (median dose, 600 mg daily) were superior to placebo (weighted mean difference on a 0-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 192 publications
(100 citation statements)
references
References 73 publications
2
93
0
3
Order By: Relevance
“…Tremont-Lukats et al recently confirmed mexiletine's analgesic efficacy for neuropathic pain in a meta-analysis. 2 However, the mean decrease on a 100-point VAS score was only 11, leading experts to question mexiletine's clinical use and specifically call for an integrated assessment of mexiletine's efficacy and side effects. 3 However, historically there has been no consensus on how to evaluate the overall clinical performance of an analgesic drug such as mexiletine, one that has inconsistent analgesia and common overwhelming side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tremont-Lukats et al recently confirmed mexiletine's analgesic efficacy for neuropathic pain in a meta-analysis. 2 However, the mean decrease on a 100-point VAS score was only 11, leading experts to question mexiletine's clinical use and specifically call for an integrated assessment of mexiletine's efficacy and side effects. 3 However, historically there has been no consensus on how to evaluate the overall clinical performance of an analgesic drug such as mexiletine, one that has inconsistent analgesia and common overwhelming side effects.…”
Section: Discussionmentioning
confidence: 99%
“…1 Tremont-Lukats et al recently confirmed mexiletine's analgesic efficacy for neuropathic pain in a meta-analysis. 2 However, mexiletine induces nausea in up to 40% of patients and dizziness in up to 26% of patients.…”
Section: Introductionmentioning
confidence: 99%
“…In controlled studies, intravenous lidocaine was effective in different Pain Manag. (2016) 6(4) 390 REviEW Okifuji, Gao, Bokat & Hare future science group dosages and regimens for the treatment of a variety of neuropathic pain states such as poststroke pain, peripheral neuropathy, diabetic neuropathy and complex regional pain syndrome I and II [130].…”
Section: • Lidocaine Infusionmentioning
confidence: 99%
“…Intravenous lidocaine promotes a decrease in spinal sensitization, reducing spontaneous pain, dysesthesia, hyperalgesia and allodynia [129]. In controlled studies, intravenous lidocaine was effective in different REviEW Okifuji, Gao, Bokat & Hare future science group dosages and regimens for the treatment of a variety of neuropathic pain states such as poststroke pain, peripheral neuropathy, diabetic neuropathy and complex regional pain syndrome I and II [130].…”
Section: • Lidocaine Infusionmentioning
confidence: 99%
See 1 more Smart Citation